Harnessing sugarcane bagasse for bioenergy production: Current status, optimization, and future directions - Ojo-kupoluyi, O.J.; Dele-Afolabi, T.T.; Tahir, S.M. (Elsevier, 2024)
The renewable energy sector is undergoing a revolution, driven by the need for sustainable resources. Among these, sugarcane bagasse (SCB) stands out as a promising candidate for bioenergy, capable of generating elec- tricity, bioethanol, and biogas. However, SCB storage and utilization face significant challenges due to its high moisture content (48–52%) after sugarcane crushing. This review explores the limitations of conventional SCB drying methods and introduces solar drying as an energy-efficient and eco-friendly alternative. The conversion of SCB to bioethanol is further complicated by its recalcitrant structure, necessitating costly and sometimes toxic pre-treatment processes. This comprehensive study examines the current landscape and advancements in SCB pre-treatment techniques during bioenergy production. Additionally, it discusses innova- tive strategies to optimize cogeneration systems, aiming to boost surplus power export to the grid. By shedding light on these cutting-edge developments, this review aims to inspire further research and innovation in the quest for sustainable bioenergy solutions.